OUTCOME OF GPLLB/LLLA INHIBITORS IN TOTALLY OCCLUDED CORONARY ARTERY IN PATIENTS PRESENTING WITH ACUTE MYOCARDIAL INFARCTION LATE FOR THROMBOLYSIS OR PRIMARY PERCUTANEOUS CORONARY INTERVENTION - Fahad Khalid; Muhammad Fareed Khan; Wahab Anwar; Muhammad Fasihullah Khan; Iqbal, Muhammad Hasnain; Naveed Yaqoob (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute coronary ischemia is one of the most fatal cardiovascular events, presenting with tremendously high morbidity and mortality, especially in cases involving a completely occluded artery, leading to acute myocardial infarction (AMI). The study aimed to ascertain the efficacy and safety of glycoprotein IIb/IIIa (GP IIb/IIIa) inhibitors in Pakistani patients who present late for thrombolysis or primary percutaneous coronary intervention (PCI). Method: The trial was conducted at a tertiary care hospital in Islamabad, including 200 patients, with GP IIb/IIIa inhibitors used in 40% of infarct-related artery (IRA) cases. Results: The analysis revealed that GP IIb/IIIa inhibitors reduced major adverse cardiac events (MACE) by 9%, recurrent myocardial infarction (MI) by 7.5%, and improved thrombus resolution by 25%, as well as myocardial salvage by 12%. However, there was a higher rate of bleeding complications (p < .05) associated with their use. No other significant adverse events, such as in-hospital mortality, length of stay, or renal complications, were identified. Conclusions: These results suggest that GP IIb/IIIa inhibitors should not be used as a one-size-fits-all therapy. Proper patient selection, along with robust monitoring under dose-adjusted Eptifibatide or Tirofiban infusion regimens to target coagulation levels appropriately, is crucial. Although this treatment could be valuable in managing AMI, particularly in regions where advanced cardiac care is less accessible, further large-scale, multicenter studies are needed to determine its long-term safety and efficacy. This study provides a framework for further investigations into the use of GP IIb/IIIa inhibitors in similar patient populations.